2020
DOI: 10.21203/rs.3.rs-15973/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevention of Mother-to-Child Transmission (PMTCT) of HIV in Iran: Situation Analysis of the Pilot Phase

Abstract: Background The reproductive health and Prevention of Mother-to-Child Transmission of HIV (PMTCT) programs in Iran were integrated as a pilot project in September 2014.This study aims to provide a comprehensive evaluation and situation analysis of the PMTCT programme in Iran.Methods Pilot phase of PMTCT was launched in early September 2014 in selected centers including 170 health centers and 40 hospitals affiliated to medical universities of 16 provinces of Iran. In each medical university, a researcher-made ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…These gender diffe rences are largely explained by social and behavioral factors. In addition to the regularity and high commitment of wom en versus men in adherence to treatment, antiretroviral treatment can be provided to prevent mothertochild trans mission, which has been included in the national guidelines for care and treatment since 2016 [20].…”
Section: Discussionmentioning
confidence: 99%
“…These gender diffe rences are largely explained by social and behavioral factors. In addition to the regularity and high commitment of wom en versus men in adherence to treatment, antiretroviral treatment can be provided to prevent mothertochild trans mission, which has been included in the national guidelines for care and treatment since 2016 [20].…”
Section: Discussionmentioning
confidence: 99%
“…These gender differences are largely explained by social and behavioral factors. In addition to the regularity and high commitment of women versus men in adherence to treatment, antiretroviral treatment can be provided to prevent the transmission of HIV from mother to infant, which has been included in the national guidelines for care and treatment since 2016 (21).…”
Section: Discussionmentioning
confidence: 99%
“…[11][12] Besides, numerous institutions, such as the World Health Organization, National Academies Practice, and the American Public Health Association, have indicated their support for IPE. 4,9,13 The previous literature reports how IPE, reviews of conferences, and regional IPE networks are becoming more common in many countries. A systematic review and meta-analysis of interprofessional education in healthcare revealed a statistically significant outcome of intervention by the IPE program in healthcare (the effect summary value of 1.37 with a confidence interval of 0.92 -1.82).…”
Section: Introductionmentioning
confidence: 99%